More telescope power : all new activities and projects for young astronomers - Matloff, Gregory L.; Bangs, Constance (New York : J. Wiley, 2002)
Presents various astronomy activities using a telescope, including constructing a simple telescope, tracking satellites, and sketching details of the moon.
Includes bibliographical references (p. 107-108) and index.
Keywords: Astronomy -- Experiments -- Juvenile literature; Telescopes -- Experiments -- Juvenile literature; Astronomy -- Experiments; Experiments; Telescopes -- Experiments